The Mediating Role of Positive Organizational Behavior in the Relationship Between Servant Leadership and Employee Engagement in Kathmandu’s Five-Star Hotels - Ale, Dilip; Chapagain, Ravi (Nepalese Journal of Hospitality and Tourism Management, 2026)
The hospitality sector is highly reliant upon employee engagement to achieve optimal levels of service quality and organizational success. The current research study explores the servant leadership, positive organizational behavior and employee engagement relationships in five-star hotels located in Kathmandu, Nepal. A quantitative descriptive analytical research design was implemented, and data were collected from 388 employees working at three selected 5-star hotels using structured questionnaires. The relationships and mediation effects were tested using Partial Least Squares Structural Equation Modelling. The findings of the current study show a substantial and positive direct relationship between servant leadership and employee engagement; however, the findings do not support that servant leadership has a direct or positive effect on positive organizational behavior or that positive organizational behavior directly predicts employee engagement. Therefore, positive organizational behavior does not mediate the relationship between servant leadership and employee engagement. Furthermore, the statistical results of the structural model indicate a low level of variance in employee engagement indicating that leadership behavior have a greater direct influence over engagement than psychological resources within the hospitality sector. It is clear from this research that developing servant leadership capabilities will allow for the improvement of employee engagement levels within luxury hotels through the means of employee becoming engaged at work through the development of their own engagement level. Future research should look to incorporate various contextual and organizational elements to better explain employee engagement levels in the hospitality industry.